2020
DOI: 10.1109/access.2020.2984319
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Learning-Based Bilinear Subspace Identification for Online Modeling and Predictive Control of a Complicated Industrial Process

Abstract: In this paper, a recursive learning based bilinear subspace identification (R-B-SI) algorithm is proposed for online modeling and data-driven predictive control of blast furnace (BF) ironmaking process with strong nonlinear time-varying dynamics. Different from the existing linear SI algorithms, the R-B-SI algorithm can make full use of the process data information by adding the Kronecker product term of input data and the Kronecker product term between input and output data into the data block Hankel matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…are the control input vector, the weight output vector and the state vector of the system, respectively, đ›Ÿ(y, u(k)) is the output PDF, h is the dimension of the input. The matrices A, B, C, N i are the system matrices to be identified, which are identified by bilinear subspace identification 28 in this paper.…”
Section: Modeling Of Bilinear Stochastic Distribution Systemsmentioning
confidence: 99%
“…are the control input vector, the weight output vector and the state vector of the system, respectively, đ›Ÿ(y, u(k)) is the output PDF, h is the dimension of the input. The matrices A, B, C, N i are the system matrices to be identified, which are identified by bilinear subspace identification 28 in this paper.…”
Section: Modeling Of Bilinear Stochastic Distribution Systemsmentioning
confidence: 99%
“…The melting points of some of the most commonly employed metals and refractories are depicted in Figure 2. [17,18]. As shown in Figure 3, if melting point is the only criterion, a range of refractory materials are suitable.…”
Section: Stack Regionmentioning
confidence: 99%
“…In Figure 12, it is shown that ACF and PACF of #1 BF are terminated within the confidence band at 5 and 2 orders respectively. Therefore, the prototype of this energy model for #1 BF can be set as ARMA (2,5). 2000 samples of seven BFs have been captured from an ironmaking plant with a production of ten million tons per year.…”
Section: B Practical Preparation For Optimizationmentioning
confidence: 99%
“…To enhance the transparency of soft-margin support vector machine, Chen et al proposed a novel algorithm to solve the shortcomings of black box model in BF [4]. Be-sides, Zhou et al proposed a bilinear subspace identification algorithm based on recursive learning to learn the nonlinear time varying dynamics of a BF [5]. Moreover, Li et al judged the transformation tendency of silicon content in hot metal by fuzzy classifier [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation